Cost-effectiveness and satisfaction following arthroscopic rotator cuff repair: does age matter?. (July 2019) - Nicholson, J. A.; Searle, H. K. C.; MacDonald, D.; McBirnie, J.
Abstract : Aims: The aim of this study was to investigate the influence of age on the cost-effectiveness of arthroscopic rotator cuff repair. Patients and Methods: A total of 112 patients were prospectively monitored for two years after arthroscopic rotator cuff repair using the Disabilities of the Arm, Shoulder and Hand questionnaire (DASH), the Oxford Shoulder Score (OSS), and the EuroQol five-dimension questionnaire (EQ-5D). Complications and use of healthcare resources were recorded. The incremental cost-effectiveness ratio (ICER) was used to express the cost per quality-adjusted life-year (QALY). Propensity score-matching was used to compare those aged below and above 65 years of age. Satisfaction was determined using the Net Promoter Score (NPS). Linear regression was used to identify variables that influenced the outcome at two years postoperatively. Results: A total of 92 patients (82.1%) completed the follow-up. Their mean age was 59.5 years (sd 9.7, 41 to 78). There were significant improvements in the mean DASH (preoperative 47.6 vs one-year 15.3; p < 0.001) and OSS scores (26.5 vs 40.5; p < 0.001). Functional improvements were maintained with no significant change between one and two years postoperatively. The mean preoperative EQ-5D was 0.54 increasing to 0.81 at one year (p < 0.001) and maintained at 0.86, two years postoperatively. There was no significant difference between those aged below or above 65 years of age with regards to postoperative shoulder function or EQ-5D gains. Smoking was the only characteristic that significantly adversely influenced the EQ-5D at two years postoperatively (p = 0.005). A total of 87 were promoters and five were passive, giving a mean NPS of 95 (87/92). The total mean cost per patient was £3646.94 and the mean EQ-5D difference at one year was 0.2691, giving a mean ICER of £13 552.36/QALY. At two years, this decreased further to £5694.78/QALY. This was comparable for those aged below or above 65 years of age (£5209.91 vs £5525.67). Smokers had an ICER that was four times more expensive. Conclusion: Arthroscopic rotator cuff repair results in excellent patient satisfaction and cost-effectiveness, regardless of age. Cite this article: Bone Joint J 2019;101-B:860–866.